DEIKSIS PERSONA DALAM FILM PRIDE AND PREJUDICE KARYA JOE WRIGHT ( ANALISIS PRAGMATIK ) - Dopong, Hana Lawatania; Jansen, Frieda Th.; Lasut, Theresia M.C (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â ABSTRACTThe title of this research is â€œDeiksis Persona dalam Film Pride and Prejudice Karya Joe Wright (Analisis Pragmatik)â€. This study is an attempt to describe, classify, and analyze person deixis found in the film Pride and Prejudice. The aim of this research is to identify, classify the type and analyze the function of person deixis used in the film. This research uses descriptive method and pragmatic analysis. The data of deixis have been taken from the sentences in the film Pride and Prejudice and analyzed them by using Levinsonâ€™s theory. The types of person deixis are: first person deixis, second person deixis, and third person deixis. The result of this study shows that person deixis in this film are first person deixis: I, me, my, mine, we, our, us; second person deixis: you, your, yours; and third person deixis: they, their, them, it, he, his, him, she, her.Keywords: Person deixis, Pragmatic Analysis, Film Pride and Prejudice